Studies on the acyloin reaction : development of novel N-heterocyclic carbene catalysts - O'Toole, Sarah (Trinity College (Dublin, Ireland). School of Chemistry, 2010)
The benzoin condensation reaction involves the catalytic dimerisation of two aldehydes to yield acyloins (a-hydroxy ketones), which are highly useful building blocks for the synthesis of heterocycles, natural products, agrochemicals and pharmaceutical drugs. In the 1940s thiazolium salts, in the presence of base, were found to act as catalysts for the benzoin condensation. In an effort to impart stereoselectivity to this reaction various chiral heteroazolium (thiazolium and triazolium) salt precatalysts have been developed over the past few decades, with the first asymmetric benzoin condensation reaction emerging in 1966.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.